The girl behind the wall - Robotham, Mandy (Avon, 2021)
After the Berlin Wall goes up, Karin is caught in East Berlin and separated from her twin sister, but when she escapes and is reunited with her sister, she must decide if she is going to stay or return to Otto, the man she left behind.